BCG Therapy for Type 1 Diabetes: Restoration of Balanced Immunity and Metabolism. (February 2019) - Kühtreiber, Willem M.; Faustman, Denise L.
Abstract : The bacillus Calmette–Guerin (BCG) vaccine is a microorganism developed as a vaccine for tuberculosis 100 years ago and used as therapy for bladder cancer 40 years ago. More recently, BCG has shown therapeutic promise for type 1 diabetes (T1D) and several other autoimmune diseases. In T1D, BCG restored blood sugars to near normal, even in patients with advanced disease of >20 years duration. This clinically important effect may be driven by resetting of the immune system and the shifting of glucose metabolism from overactive oxidative phosphorylation, a state of minimal sugar utilization, to aerobic glycolysis, a state of high glucose utilization, for energy production. The mechanistic findings support the Hygiene Hypothesis and reveal the immune and metabolic synergy of mycobacterial reintroduction in modern humans. Highlights: The BCG vaccine is an attenuated form of mycobacterium originally developed >100 years ago for tuberculosis prevention. Its safety record is unsurpassed. This vaccine is now being investigated as a therapy for type 1 diabetes (T1D) and other autoimmune diseases to restore the immune balance. Repeated BCG vaccinations in long-term diabetics can restore blood sugars to near normal by resetting the immune system and by increasing glucose utilization through a metabolic shift to aerobic glycolysis, a high-glucose-utilization state. BCG-treated subjects given at least two vaccines do not experience restoration of blood sugars until about 3 years later, but once the blood sugars return to normal, the therapeutic effect endures beyond 5 years. T1D subjects prior to BCG treatment have an immune system dominated by oxidative phosphorylation, a low-glucose-utilization state that predominantly utilizes the Krebs cycle for energy. Based on the Hygiene Hypothesis, lifelong underexposure to pathogens could account for the predominance of oxidative phosphorylation in untreated T1D. Because the BCG-induced restoration of glucose utilization is through regulated cellular utilization of sugar, episodes of hypoglycemia with near-normal blood sugars are rarely reported.